Middle East Respiratory Syndrome Coronavirus - Al-Tawfiq, Jaffar A.; Azhar, Esam I.; Memish, Ziad A.; Zumla, Alimuddin (Seminars in Respiratory and Critical Care Medicine, 2021)
The past two decades have witnessed the emergence of three zoonotic coronaviruses which have jumped species to cause lethal disease in humans: severe acute respiratory syndrome coronavirus 1 (SARS-CoV-1), Middle East respiratory syndrome coronavirus (MERS-CoV), and SARS-CoV-2. MERS-CoV emerged in Saudi Arabia in 2012 and the origins of MERS-CoV are not fully understood. Genomic analysis indicates it originated in bats and transmitted to camels. Human-to-human transmission occurs in varying frequency, being highest in healthcare environment and to a lesser degree in the community and among family members. Several nosocomial outbreaks of human-to-human transmission have occurred, the largest in Riyadh and Jeddah in 2014 and South Korea in 2015. MERS-CoV remains a high-threat pathogen identified by World Health Organization as a priority pathogen because it causes severe disease that has a high mortality rate, epidemic potential, and no medical countermeasures. MERS-CoV has been identified in dromedaries in several countries in the Middle East, Africa, and South Asia. MERS-CoV-2 causes a wide range of clinical presentations, although the respiratory system is predominantly affected. There are no specific antiviral treatments, although recent trials indicate that combination antivirals may be useful in severely ill patients. Diagnosing MERS-CoV early and implementation infection control measures are critical to preventing hospital-associated outbreaks. Preventing MERS relies on avoiding unpasteurized or uncooked animal products, practicing safe hygiene habits in health care settings and around dromedaries, community education and awareness training for health workers, as well as implementing effective control measures. Effective vaccines for MERS-COV are urgently needed but still under development.
Keywords: coronavirus; epidemic infections; MERS coronavirus